2004
DOI: 10.1007/s00018-003-3309-z
|View full text |Cite
|
Sign up to set email alerts
|

Where, when and how much: regulation of myelin proteolipid protein gene expression

Abstract: The myelin proteolipid protein (PLP) gene ( Plp) encodes the most abundant protein found in myelin from the central nervous system (CNS). Expression of the gene is regulated in a spatiotemporal manner with maximal levels of expression occurring in oligodendrocytes during the active myelination period of CNS development, although other cell types in the CNS as well as in the periphery can express the gene to a much lower degree. In oligodendrocytes, Plp gene expression is tightly regulated. Underexpression or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 149 publications
1
7
0
Order By: Relevance
“…The gene is highly expressed in oligodendrocytes and olfactory ensheathing cells (OECs) (Griffiths et al, 1995; Dickinson et al, 1997), and to a lesser extent in select populations of neurons and additional cell types in the periphery (reviewed in Wight and Dobretsova, 2004). The gene is located on the X chromosome with seven major exons distributed across nearly 16 kb of DNA in human.…”
Section: Introductionmentioning
confidence: 99%
“…The gene is highly expressed in oligodendrocytes and olfactory ensheathing cells (OECs) (Griffiths et al, 1995; Dickinson et al, 1997), and to a lesser extent in select populations of neurons and additional cell types in the periphery (reviewed in Wight and Dobretsova, 2004). The gene is located on the X chromosome with seven major exons distributed across nearly 16 kb of DNA in human.…”
Section: Introductionmentioning
confidence: 99%
“…The protein has been shown to recognize a target motif in the promoter of the human myelin PLP (proteolipid protein) gene ( PLP1 ) where it seemingly functions as a transcriptional activator (Berndt et al, 2001). PLP1/Plp1 gene expression is regulated in a spatiotemporal manner and, in oligodendrocytes, is responsible for nearly half the protein in CNS (central nervous system) myelin from adults (reviewed in Wight and Dobretsova, 2004). Categorization of YY1 as an activator of human PLP1 gene transcription stems from studies by Berndt et al showing that: (i) it binds selectively to a YY1 target site located within a region of the PLP1 promoter referred to as site 3 [positions −130 to −104 relative to the transcription start point (+1)] (Berndt et al, 2001), which previously had been shown to bind nuclear protein(s) in a sequence-specific manner (Berndt et al, 1992); (ii) deletion–transfection analysis in glial cells using various PLP1 promoter driven reporter constructs revealed a dramatic decrease in reporter gene activity when site 3 was deleted along with another, unrelated, protein binding site (site 2; positions −76 to −50) (Berndt et al, 1992); (iii) the level of expression of a PLP1 -reporter gene construct that contains PLP1 sequences from −1088 to +85 was increased when human (SVG) or rat (CG4) glial cell lines were co-transfected with a YY1 expression plasmid, but not with an analogous construct having a mutant site 3 that disrupts YY1 binding (Berndt et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the gene in mouse and man is quite similar (reviewed in Wight and Dobretsova, 2004). The 5′-flanking DNA is highly conserved between the two species, demonstrating 50% identity for the proximal 1.3 kb of sequence and 91% identity among the initial 135 nucleotides using the algorithm of Myers and Miller (1988).…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of being the most abundant protein in the CNS, myelin gene expression is regulated in a spatiotemporal manner with maximal levels of expression occurring in oligodendrocytes during the active myelination period of CNS development (Wight and Dobretsova, 2004). It has been documented through numerous studies in mouse models that overexpression or deficiency of one or more myelin component in the CNS can result in induction of compensatory protein clearance mechanisms such as increase in numbers of CD11b positive microglia, phagocytosis and subsequent autoimmune inflammation (Ip et al, 2008; Karim et al, 2007; Leder et al, 2007; Muller et al, 2007).…”
Section: Discussionmentioning
confidence: 99%